Drug-Induced Lichen Planus Pigmentosus-Inversus Treated with Propolis Cream. A Case Report - Francisco Nelson Matos Figueredo; Odisa Mildres Cortés Ros; Lourdes Villacrés Medina (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2013)
Lichen planus has numerous clinical variants; one of them is lichen planus pigmentosus which is rarely mentioned in the medical literature. When located in the skin folds, it is known as lichen planus pigmentosus-inversus. In order to communicate a rare variant of lichen planus and its first presentation associated with drugs, we report the case of a 51 year-old mixed-race female patient from Latin America who was treated in the Department of Dermatology at the Celia Sanchez Manduley Clinical-Surgical Hospital in Granma. She presented with pigmented lesions in the inframammary folds that had evolved over several years. The clinical diagnosis was confirmed by histopathological elements. Some dermatoses with similar characteristics were dismissed. Treatment with propolis cream was beneficial.